Classic car : the definitive visual history - Gurdon, Martin; Long, David; Noakes, Andrew; Rees, Chris (DK Publishing, 2023)
"Featuring more than 250 iconic models from the 1940s to the 1980s, Classic Car is a celebration of the most beautiful and innovative cars produced since the birth of mass car-ownership. Meet the designers behind these amazing machines and discover the history of the manufacturers that have brought them to life"--